2004
DOI: 10.1002/bdra.20079
|View full text |Cite
|
Sign up to set email alerts
|

SB‐236057: Critical window of sensitivity study and embryopathy of a potent musculoskeletal teratogen

Abstract: SB-236057 is speculated to alter paraxial mesoderm programming. Many of the skeletal malformations may be caused secondarily from musculature abnormalities, suggesting that the myotome may be particularly sensitive to the compound. Furthermore, the finding that peripheral nerve trajectories were altered along the axis and in the limb suggests that SB-236057 may alter early embryonic signaling pathways necessary for neuronal differentiation/axonal guidance that occur subsequently in embryo-fetal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…If the distribution of induced cell death and/or inhibited growth is not uniform, disproportionate growth can result. Skeletal malformations can result from disruption of the growth of surrounding muscle (Augustine-Rauch, et al, 2004;Braun, et al 1992;Dickman et al, 1999;Henderson et al, 1999) as well as from perturbations of chondrogenesis and ossification (Karsenty, 1998). A disproportionate growth mechanism is consistent with the types of skeletal malformations caused by artesunate.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…If the distribution of induced cell death and/or inhibited growth is not uniform, disproportionate growth can result. Skeletal malformations can result from disruption of the growth of surrounding muscle (Augustine-Rauch, et al, 2004;Braun, et al 1992;Dickman et al, 1999;Henderson et al, 1999) as well as from perturbations of chondrogenesis and ossification (Karsenty, 1998). A disproportionate growth mechanism is consistent with the types of skeletal malformations caused by artesunate.…”
Section: Discussionmentioning
confidence: 89%
“…Other seemingly unrelated agents have been associated with a syndrome of shortening, bending, and thickening of long bones in rats sometimes associated with bending of the scapula similar to that caused by artesunate. These agents are the antidiabetic sulfonylurea drugs glimepiride (Baeder, 1993; USFDA (Summary Basis of Approval for Amaryl, glimepiride tablets)), 1995; Physician's Desk Reference, 2002a) and glyburide (Physician's Desk Reference, 2002b), the antidiabetic meglitinide drug repaglinide (Viertel and Guttner, 2000), the manganese chelator mangafodipir trisodium (Treinen et al, 1995), and the 5-HT1B receptor inverse agonist (Augustine-Rauch et al, 2004). The latter agent also caused decreased fetal weight at the teratogenic dose.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other genomics efforts focused on pathway detection, one using GWAS data and the other CNV data, have independently implicated impaired neuronal projection and axonal guidance [35,44] as mechanisms of chief interest. These are environmentally sensitive processes beginning early in brain development [104,105] that could certainly affect synaptic functioning downstream. Of course, the high likelihood of an in utero origin of autism in no way rules out the potential for etiologic and prognostic influences after birth, but the design and implementation of etiologic research focused on the prenatal period would appear strongly justified.…”
Section: Reviewmentioning
confidence: 99%
“…In addition, an anterior to posterior gradient of severity was observed in the affected fetal skeletons, with the more severe malformations, such as agenesis of the lumbar, sacral, and coccygeal vertebrae, located posteriorly along the axis. An anterior‐posterior gradient of spinal cord malformations was also observed, suggesting that SB‐236057 may disrupt processes occurring during early organogenesis such as somitogenesis and neurulation (Solomon et al, 2003; Augustine‐Rauch et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A tailored in vivo study was conducted in rats to identify the critical developmental window of compound sensitivity (Augustine‐Rauch et al, 2004). The results of this study demonstrated that the “critical window” of developmental sensitivity spanned between days 6 and 11 postcoitus (pc, relative to day 0 at insemination).…”
Section: Introductionmentioning
confidence: 99%